An analysis of the labour market integration of immigrants : examining the role of gender, ethnicity, discrimination and recession - Kingston, Gillian (Trinity College (Dublin, Ireland). Department of Sociology, 2017)
This thesis focuses on the labour market integration of migrants between 2004 and 2011, a period of unprecedented change in Irish society. The work analyses some of the factors that may influence migrants’ labour market integration- namely gender, ethnicity, discrimination and recession. By drawing on data from two rich surveys, and including analysis of different labour market outcomes among several immigrant groups, over time, and across countries, the strength of the study is that it can examine labour market integration from various angles, with the aim that combining these aspects provides a deeper insight into the factors that drive integration and inequality. The work incorporates four separate empirical chapters and an introduction and conclusion chapter, from human capital theory, compositional hypotheses are derived, which predict that differences in labour market outcomes can be attributed to differences in human capital among groups. From discrimination theories, contextual hypotheses are derived, which examine whether inequalities in outcomes exist, and can be ascribed to in-group preferences and prejudices against groups. Overall, the study finds evidence of success for some migrant groups, and evidence of marked and ongoing penalties for others. Chapter two examines whether immigrants’ experience higher levels of self-reported labour market discrimination than natives. This study is the first, to my knowledge, to examine changes in migrants’ self-reported labour market discrimination over the course of the Great recession. The work finds that migrants’ do experience higher levels of discrimination, and discrimination varies among national-ethnic groups, in particular the Black African group report experiencing high levels of discrimination in the workplace, and when looking for work. It is interesting to find that discrimination did not increase in the context of recession, and overall discrimination when looking for work actually decreased. The study also finds evidence of the integration of some immigrant groups in the labour market, particularly for White EU-13 and White UK migrants’, groups who have a more established history of migration to Ireland and are more culturally similar. The analysis in chapter three extends on this work, and examines whether immigrant groups experience inequalities in their labour market outcomes compared to natives, especially in the context of recession. A further contribution of this work is that it extends on knowledge of ethnicity, and the outcomes of the ‘non-EU’ group in Ireland. Most of the research and academic discussion on migration in Ireland has not included ethnicity, and this work was the first in Ireland to examine ethnic disadvantage over the recession. Findings show that both the Black African and White New Member States groups experience marked disadvantage in their economic outcomes in both 2004 and 2010. However, disadvantage only increased above and beyond that of natives for male migrants’ from the New Member States. Chapter four examines gender differences in the occupational attainment of recent Polish migrants’ in Ireland. Another contribution of this work is that it expands on our understanding of gender differences in migrants’ labour market incorporation, and employs Blinder-Oaxaca decomposition methods to examine in more detail the factors that influence gender differences. Findings in Ireland do not reveal a significant gap in male and female occupational attainment, however females experience disadvantage in returns to their human capital, and results do not provide support for traditional human capital theories of lower female capital. It is suggested that the labour market situation in Ireland at the time of study may be a contributing reason for parity in migrants’ occupational attainment. Chapter five of the analysis extends on this work and examines gender differences in the occupational attainment of recent Polish migrants in Germany, the UK and the Netherlands, to place Irish findings in an international context. To date no study has assessed the gender differentials in the occupational outcomes of the same migrant group across countries. The comparative findings show that females experience lower occupational attainment in the Netherlands, Germany, and the UK, further cementing the idea that findings in Ireland are related to the economic situation at the time of study. The finding of female advantage in human capital endowments (in Germany and Ireland) and parity in human capital endowments (in the Netherlands and the UK) calls into question the more general hypotheses on females’ lower investment in human capital. The comparative analysis finds weak support for the effect of family, and no support for the effect of ‘tied mover’ status on female outcomes across countries. In all countries of study, a substantial portion of the gender gap in occupational attainment remains unexplained and cannot be attributed to differences in human capital, or due to gender differences in the effect of children and family. This thesis focuses on the labour market integration of migrants between 2004 and 2011, a period of unprecedented change in Irish society. The work analyses some of the factors that may influence migrants’ labour market integration- namely gender, ethnicity, discrimination and recession. By drawing on data from two rich surveys, and including analysis of different labour market outcomes among several immigrant groups, over time, and across countries, the strength of the study is that it can examine labour market integration from various angles, with the aim that combining these aspects provides a deeper insight into the factors that drive integration and inequality. The work incorporates four separate empirical chapters and an introduction and conclusion chapter, from human capital theory, compositional hypotheses are derived, which predict that differences in labour market outcomes can be attributed to differences in human capital among groups. From discrimination theories, contextual hypotheses are derived, which examine whether inequalities in outcomes exist, and can be ascribed to in-group preferences and prejudices against groups. Overall, the study finds evidence of success for some migrant groups, and evidence of marked and ongoing penalties for others. Chapter two examines whether immigrants’ experience higher levels of self-reported labour market discrimination than natives. This study is the first, to my knowledge, to examine changes in migrants’ self-reported labour market discrimination over the course of the Great recession. The work finds that migrants’ do experience higher levels of discrimination, and discrimination varies among national-ethnic groups, in particular the Black African group report experiencing high levels of discrimination in the workplace, and when looking for work. It is interesting to find that discrimination did not increase in the context of recession, and overall discrimination when looking for work actually decreased. The study also finds evidence of the integration of some immigrant groups in the labour market, particularly for White EU-13 and White UK migrants’, groups who have a more established history of migration to Ireland and are more culturally similar. The analysis in chapter three extends on this work, and examines whether immigrant groups experience inequalities in their labour market outcomes compared to natives, especially in the context of recession. A further contribution of this work is that it extends on knowledge of ethnicity, and the outcomes of the ‘non-EU’ group in Ireland. Most of the research and academic discussion on migration in Ireland has not included ethnicity, and this work was the first in Ireland to examine ethnic disadvantage over the recession. Findings show that both the Black African and White New Member States groups experience marked disadvantage in their economic outcomes in both 2004 and 2010. However, disadvantage only increased above and beyond that of natives for male migrants’ from the New Member States. Chapter four examines gender differences in the occupational attainment of recent Polish migrants’ in Ireland. Another contribution of this work is that it expands on our understanding of gender differences in migrants’ labour market incorporation, and employs Blinder-Oaxaca decomposition methods to examine in more detail the factors that influence gender differences. Findings in Ireland do not reveal a significant gap in male and female occupational attainment, however females experience disadvantage in returns to their human capital, and results do not provide support for traditional human capital theories of lower female capital. It is suggested that the labour market situation in Ireland at the time of study may be a contributing reason for parity in migrants’ occupational attainment. Chapter five of the analysis extends on this work and examines gender differences in the occupational attainment of recent Polish migrants in Germany, the UK and the Netherlands, to place Irish findings in an international context. To date no study has assessed the gender differentials in the occupational outcomes of the same migrant group across countries. The comparative findings show that females experience lower occupational attainment in the Netherlands, Germany, and the UK, further cementing the idea that findings in Ireland are related to the economic situation at the time of study. The finding of female advantage in human capital endowments (in Germany and Ireland) and parity in human capital endowments (in the Netherlands and the UK) calls into question the more general hypotheses on females’ lower investment in human capital. The comparative analysis finds weak support for the effect of family, and no support for the effect of ‘tied mover’ status on female outcomes across countries. In all countries of study, a substantial portion of the gender gap in occupational attainment remains unexplained and cannot be attributed to differences in human capital, or due to gender differences in the effect of children and family.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin